2011 Triennial Surveillance Review : External Study. (Policy Papers; Policy Paper, 2011)
External study prepared by Stephen Pickford, former IMF/World Bank Executive Director for the United Kingdom and former Managing Director of International and Europe at H.M. Treasury and G-20 Finance Deputy, United Kingdom: Surveillance (both bilateral and multilateral) is a key instrument for the Fund's crisis prevention role, analyzing economic developments and policies at national, regional and global levels. It also identifies risks and vulnerabilities, and forms the main basis for the Fund's discussions with policy-makers.